Knowledge reduction in Indonesian and Japanese textbooks on the concept of area in elementary school: A didactical transposition study - Muhaimin, Lukman Hakim; Suryadi, Didi; Dasari, Dadan; Juandi, Dadang; Pahmi, Samsul; Yulianti, Sri (Indonesian Journal of Science and Mathematics Education, 2025)
The concept of area is fundamental to geometry and essential for applications in various fields, including physics, engineering, and data analysis. This study examines the gap between mathematicians’ views on area and its presentation in Indonesian and Japanese elementary textbooks, as well as its impact on student learning. Using the Anthropological Theory of Didactics and a qualitative phenomenological design, the analysis focuses on chapters discussing the area, applying a three-stage content analysis to identify conceptual components, formula presentations, shape variations, and task types. This analysis is supported by quantitative indicators, such as the task variation index and proportions of exploratory versus procedural tasks. The findings indicate that Japanese textbooks employ a more systematic and comprehensive didactic approach, offering a range of tasks, exploratory methods, and logical sequencing that promote independent learning. In contrast, Indonesian textbooks rely on repetitive, limited cut-and-paste methods, which may lead to a rigid understanding and learning obstacles. The study suggests the need for a critical evaluation of textbooks and more conceptually coherent learning designs, aligned with mathematical principles. It recommends task designs that integrate exploration and reasoning, consistent formula derivation, and broader variations of shapes to reduce learning barriers.